Oral administration of the β-glucan produced by Aureobasidium pullulans ameliorates development of atherosclerosis in apolipoprotein E deficient mice. (October 2015) - Aoki, Shiho; Iwai, Atsushi; Kawata, Koji; Muramatsu, Daisuke; Uchiyama, Hirofumi; Okabe, Mitsuyasu; Ikesue, Masahiro; Maeda, Naoyoshi; Uede, Toshimitsu
Highlights: Aureobasidium pullulans -derived β-glucan (AP-PG) is known to be an immunomodulator. Apolipoprotein E deficient (ApoE) mice spontaneously develop atherosclerosis. AP-PG is effective in ameliorating development of atherosclerosis in the model mice. AP-PG administration reduces oxidized low-density lipoprotein cholesterol levels. Oral administration of AP-PG ameliorates vascular accumulation of macrophages. Abstract: The Aureobasidium pullulans -produced β-glucan (AP-PG) is an immune stimulator, and believed to exhibit beneficial effects on health through its immune stimulating activity. Here, the effect of oral administration of AP-PG on high-fat diet (HFD)-induced atherosclerosis was evaluated using apolipoprotein E deficient mice, a widely used mouse model for atherosclerosis. The results demonstrated that HFD-induced development of atherosclerosis was significantly reduced in the AP-PG-treated mice when compared with that of the control mice. In serological analysis, blood levels of oxidized low-density lipoprotein cholesterol, a well-known risk factor for the development of atherosclerosis, were significantly reduced in the AP-PG-treated group of mice. Further, immunohistochemical analysis using MOMA-2 antibody showed that oral administration of AP-PG is effective in ameliorating vascular accumulation of macrophages. These data suggest the possibility that oral administration of AP-PG is effective in ameliorating HFD-induced development of atherosclerosis.